Contribution to the knowledge of the Moroccan High and Middle Atlas stoneflies (Plecoptera, Insecta) - Vinçon, Gilles (Illiesia, 2014)
Amphinemura tiernodefigueroai sp. n., endemic of the Moroccan Middle-Atlas, and Capnioneura atlasica sp. n., endemic of the Moroccan High-Atlas, are described and illustrated. The two new species are reliably separable in both sexes. Comparative descriptions are given for Amphinemura berthelemyi Vinçon, Yasri & Lounaci 2013 and Capnioneura petitpierreae Aubert 1961. Five species are new for the Middle Atlas: Nemoura lacustris Pictet 1865, Capnopsis schilleri schilleri (Rostock 1892), Leuctra franzi paenibaetica Sánchez-Ortega & Ropero-Montero, 1993, L. ketamensis Sánchez-Ortega & Azzouz 1997 and Tyrrhenoleuctra tangerina (Navás 1922) and three are new for the High-Atlas: Brachyptera algirica Aubert 1956, Protonemura dakkii Vinçon & Murányi 2009 and Capnopsis schilleri schilleri (Rostock 1892). The faunistic list of the 23 Atlas stoneflies is updated and discussed.
Keywords: entomology; stoneflies; Atlas; Plecoptera; Morocco